Terpyridine-metal complexes: effects of different substituents on their physico-chemical properties and density functional theory studies - Ehsan Ullah Mughal; Masoud Mirzaei; Amina Sadiq; Sana Fatima; Ayesha Naseem; Nafeesa Naeem; Nighat Fatima; Samia Kausar; Ataf Ali Altaf; Muhammad Naveed Zafar; Bilal Ahmad Khan (2020)
A series of different substituted terpyridine (tpy)-based ligands have been synthesized by Kröhnke method. Their binding behaviour was evaluated by complexing them with Co(II), Fe(II) and Zn(II) ions, which resulted in interesting coordination compounds with formulae, [Zn(tpy) 2 ]PF 6 , [Co(tpy) 2 ](PF 6 ) 2 , [Fe(tpy) 2 ](PF 6 ) 2 and interesting spectroscopic properties. Their absorption and emission behaviours in dilute solutions were investigated in order to explain structure–property associations and demonstrate the impact of different aryl substituents on the terpyridine scaffold as well as the role of the metal on the complexes. Photo-luminescence analysis of the complexes in acetonitrile solution revealed a transition from hypsochromic to bathochromic shift. All the compounds displayed remarkable photo-luminescent properties and various maximum emission peaks owing to the different nature of the functional groups. Furthermore, the anti-microbial potential of ligands and complexes was evaluated with docking analyses carried out to investigate the binding affinity of terpyridine-based ligands along with corresponding proteins (shikimate dehydrogenase and penicillin-binding protein) binding sites. To obtain further insight into molecular orbital distributions and spectroscopic properties, density functional theory calculations were performed for representative complexes. The photophysical activity and interactions between chromophore structure and properties were both investigated experimentally as well as theoretically.